Analisis Implementasi PSAK 108 & PSAK 234 Pada PT Indofood CBP Sukses Makmur Tbk - Mujitahid, Lalu Zainul Mujitahid; Komala, Ilhamni Intan; Putra, Komang Yudha Manggala; Rahmawati, Ida; Agustiningsih, Wulandari; Sani, Alfi (Fakultas Ekonomi dan Bisnis Unram, 2024)
This study aims to examine the conformity of the Interim Financial Statements and Segment Reports published by PT Indofood CBP Sukses Makmur Tbk. with the applicable Statement of Financial Accounting Standards (PSAK). The research method used is content analysis with a qualitative approach. The data analyzed includes segment and interim financial statements for the first quarter of 2024. The results showed that the segment financial statements of PT Indofood CBP Sukses Makmur Tbk. have met the qualitative and quantitative requirements in accordance with PSAK 108 and PSAK 234. This research contributes to the understanding of the company's compliance with accounting standards and the importance of segment reporting in decision making by investors.